Endometrial scratch in women undergoing first-time IVF treatment: a systematic review and meta-analysis of randomized controlled trials. Issue 4 (April 2022) - Metwally, Mostafa; Chatters, Robin; White, David; Hall, Jamie; Walters, Stephen
Abstract: The endometrial scratch procedure is an IVF 'add-on' sometimes provided prior to the first IVF cycle. A 2019 systematic review concluded that there was insufficient evidence to show whether endometrial scratch has a significant effect on pregnancy outcomes (including live birth rate, LBR) when undertaken prior to the first IVF cycle. Further evidence was published following this review, including the Endometrial Scratch Trial (ISRCTN23800982). The objective of the current review was to synthesize and critically appraise the evidence for the clinical effectiveness and safety of the endometrial scratch procedure in women undergoing their first IVF cycle. Databases searched include MEDLINE, Embase, CINAHL and ClinicalTrials.gov. Eligible randomized controlled trials included women undergoing IVF for the first time that reported the effectiveness and/or safety of the endometrial scratch procedure; 12 studies were included. Meta-analysis showed no evidence of a significant effect of the endometrial scratch on LBR (10 trials, odds ratio [OR] 1.17, 95% confidence interval [CI] 0.76–1.79) or other pregnancy outcomes. This review confirms that there is a lack of evidence that endometrial scratch improves pregnancy outcomes, including LBR, for women undergoing their first IVF cycle. Clinicians are recommended not to perform this procedure in individuals undergoing their first cycle of IVF.